2019
DOI: 10.1128/msystems.00177-19
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Microbiome in the European Common Cuttlefish, Sepia officinalis

Abstract: The European common cuttlefish, Sepia officinalis, is used extensively in biological and biomedical research, yet its microbiome remains poorly characterized. We analyzed the microbiota of the digestive tract, gills, and skin in mariculture-raised S. officinalis using a combination of 16S rRNA amplicon sequencing, quantitative PCR (qPCR), and fluorescence spectral imaging. Sequencing revealed a highly simplified microbiota consisting largely of two single bacterial amplicon sequence variants (ASVs) of Vibriona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The analysis of the gut microbiota diversity in cuttlefish revealed a very simple microbiome, with Mycoplasma sp. being the most abundant genus of bacteria, as observed by Lutz et al and Ramírez et al To our knowledge, it is the first study highlighting the presence of a microbiome associated with the digestive gland of cuttlefish. This microbiome is diverse when compared to the gut microbiome.…”
Section: Discussionsupporting
confidence: 64%
“…The analysis of the gut microbiota diversity in cuttlefish revealed a very simple microbiome, with Mycoplasma sp. being the most abundant genus of bacteria, as observed by Lutz et al and Ramírez et al To our knowledge, it is the first study highlighting the presence of a microbiome associated with the digestive gland of cuttlefish. This microbiome is diverse when compared to the gut microbiome.…”
Section: Discussionsupporting
confidence: 64%
“…We did not find a significant correlation between host phylogenetic distance and microbial dissimilarity, suggesting that any pattern of phylosymbiosis observed in bats is not driven by host evolution, but rather by ecological features. Investigation of microbial loads via culturebased approaches and quantitative PCR (qPCR) paired with observed spatial arrangements (e.g., via fluorescence in situ hybridization [68,69]) throughout the gut and other anatomical sites of bats will provide important insights into the nature of bat-microbe associations and whether they are sustained, functional associations or transient en-counters between bats and their environments. Analysis of morphological and physiological adaptations specific to flight in bats may also help elucidate why bats differ from nonflighted mammals with respect to the weak pattern of phylosymbiosis observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Strugnell and Nishiguchi (2007) analyzed the cephalopod intestinal microbial community in freeliving and captive Octopus minor paralarvae using nextgeneration sequencing. A recent study confirmed the microbial composition of the digestive tract, gills, and skin microbiome of Sepia officinalis (Lutz et al, 2019). The populations of S. oualaniensis are one of the most promising biological resources in the South China Sea because of their short life cycles (Zhang et al, 2010).…”
Section: Microbial Community Characteristics In Intestine and Gillmentioning
confidence: 84%